CR3 and Dectin-1 Collaborate in Macrophage Cytokine Response through Association on Lipid Rafts and Activation of Syk-JNK-AP-1 Pathway. - Juin-Hua Huang; Ching-Yu Lin; Sheng-Yang Wu; Wen-Yu Chen; Ching-Liang Chu; Gordon D Brown; Chih-Pin Chuu; Betty A Wu-Hsieh (PLoS Pathogens)
Collaboration between heterogeneous pattern recognition receptors (PRRs) leading to synergistic coordination of immune response is important for the host to fight against invading pathogens. Although complement receptor 3 (CR3) and Dectin-1 are major PRRs to detect fungi, crosstalk between these two receptors in antifungal immunity is largely undefined. Here we took advantage of Histoplasma capsulatum which is known to interact with both CR3 and Dectin-1 and specific particulate ligands to study the collaboration of CR3 and Dectin-1 in macrophage cytokine response. By employing Micro-Western Array (MWA), genetic approach, and pharmacological inhibitors, we demonstrated that CR3 and Dectin-1 act collaboratively to trigger macrophage TNF and IL-6 response through signaling integration at Syk kinase, allowing subsequent enhanced activation of Syk-JNK-AP-1 pathway. Upon engagement, CR3 and Dectin-1 colocalize and form clusters on lipid raft microdomains which serve as a platform facilitating their cooperation in signaling activation and cytokine production. Furthermore, in vivo studies showed that CR3 and Dectin-1 cooperatively participate in host defense against disseminated histoplasmosis and instruct adaptive immune response. Taken together, our findings define the mechanism of receptor crosstalk between CR3 and Dectin-1 and demonstrate the importance of their collaboration in host defense against fungal infection.